2016
DOI: 10.1177/0266666915575167
|View full text |Cite
|
Sign up to set email alerts
|

Why do smartphone shoppers help others on websites? The effects of attachments on reciprocal altruism

Abstract: Why do people help others on mobile shopping sites, even when members have never met? To answer the research question, this study applies attachment theory to investigate the relationships between formation variables (trust, enjoyment, and timesaving), transfer variables (site, group, and interpersonal attachments), and an outcome variable (reciprocal altruism). An online survey was conducted of shoppers who had purchased tourism products with smartphones. The results show that trust, enjoyment, and timesaving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 65 publications
(155 reference statements)
0
20
0
Order By: Relevance
“…Because store-evoked pleasure and arousal are closely associated with brand attachment (Orth, Limon, and Rose 2010), it is assumed that affective response positively influences attachment. Enjoyment of mobile tourism sites significantly influences attachment to the sites (Kim et al 2016b), implying that the greater the level of enjoyment as an affective response, the more closely it is related to attachment. Modern tourists' affective feelings derived from mobile phone usage enhanced by effective travel-related applications encourage them to be attached to the mobile phone while travelling (Lalicic and Weismayer 2018).…”
Section: Relationships Between Cognitive Response Affective Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Because store-evoked pleasure and arousal are closely associated with brand attachment (Orth, Limon, and Rose 2010), it is assumed that affective response positively influences attachment. Enjoyment of mobile tourism sites significantly influences attachment to the sites (Kim et al 2016b), implying that the greater the level of enjoyment as an affective response, the more closely it is related to attachment. Modern tourists' affective feelings derived from mobile phone usage enhanced by effective travel-related applications encourage them to be attached to the mobile phone while travelling (Lalicic and Weismayer 2018).…”
Section: Relationships Between Cognitive Response Affective Responsementioning
confidence: 99%
“…To measure potential tourists' attachment to tourism-related VR experiences, four items were drawn from previous research (Kim et al 2015(Kim et al , 2016b(Kim et al , 2016cOleksy and Wnuk 2017;Tussyadiah 2016) (e.g., "I am closely related to the content when using the tourism-related VR activity"). To assess visit intention to the destinations in VR tourism activities, three items were drawn from previous research by Huang et al (2013), Jang and Namkung (2009) Because 7-point Likert scales offer high reliability and discriminant validity according to Cicchetti, Showalter, and Tyrer (1985) and Preston and Colman (2000), a total of 27 items were appraised on a 7-point Likert-type scale ranging from (1) strongly disagree to (7) strongly agree.…”
Section: Measurementsmentioning
confidence: 99%
“…Altruism is the performance of an act for others without anticipating compensation (Paul, Miller, and Paul, 1993;Sundaram, Mitra, and Webster, 1998). Numerous studies have suggested that altruism is an important construct to explain individuals' willingness to share information and WOM in online social spaces (Dellarocas, Zhang, and Awad, 2007;Hung and Li, 2007;Kim et al, 2015). Many people wish to contribute to others' decision-making or help those with the same interests by spreading their consumption experience (Carman, 1992).…”
Section: Literature Review Wom Behavior On Snssmentioning
confidence: 99%
“…For online tourism products, site attachment is an important mediator between motivations (value and trust) and outcomes (altruism and loyalty) on online group-buying sites (Kim et al, 2015c). Site attachment in the context of mobile tourism shoppers is considered to be developed through positive experiences and is a mediator between antecedents (trust, enjoyment, and timesaving) and outcome variables (group and interpersonal attachment and reciprocal altruism) (Kim et al, 2015b). Site attachment explains important relationships between antecedents and consumer behaviors in online communities (Ren et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the rising importance of MTS and SNI, it will be increasingly significant for practitioners to understand the persuasive processes at work. A rapidly growing trend among tourists is to purchase and reserve tourism products and services from mobile websites accessed via mobile devices (Kim et al, 2015a;Kim et al, 2015b). Therefore, the purpose of this study is to examine the dual-routes of communication of mobile shoppers, which in turn influence consumer decision-making with respect to purchasing and reserving tourism products and services via mobile devices (smartphones and tablets).…”
Section: Introductionmentioning
confidence: 99%